2015
DOI: 10.1016/j.shaw.2015.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Work–Family Conflict, Task Interruptions, and Influence at Work Predict Musculoskeletal Pain in Operating Room Nurses

Abstract: BackgroundThe aim of this study is to examine the prevalence of musculoskeletal complaints in Swiss operating room (OR) nurses, and to investigate how work–family conflict, work interruptions, and influence at work are related to lumbar and cervical back pain.MethodsParticipants in this correlational questionnaire study included 116 OR nurses from eight different hospitals in Switzerland.ResultsWe found that 66% of the OR staff suffered from musculoskeletal problems. The most prevalent musculoskeletal complain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
44
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 71 publications
7
44
1
9
Order By: Relevance
“…85,87 There has also been new research evidence linking exposure of work-family conflicts to low back pain. 34,41,88 One possible result of how work-family life imbalance is related to low back pain may be the draining of psychological and physical resources leading to unhealthy behaviors, including alcohol and tobacco use and decreased leisure-time physical activity. 77, 89 Another postulated pathway between work-family life imbalance and low back pain is that mental strain can cause muscle tension or other physiological processes that might aggravate low back pain.…”
Section: Discussionmentioning
confidence: 99%
“…85,87 There has also been new research evidence linking exposure of work-family conflicts to low back pain. 34,41,88 One possible result of how work-family life imbalance is related to low back pain may be the draining of psychological and physical resources leading to unhealthy behaviors, including alcohol and tobacco use and decreased leisure-time physical activity. 77, 89 Another postulated pathway between work-family life imbalance and low back pain is that mental strain can cause muscle tension or other physiological processes that might aggravate low back pain.…”
Section: Discussionmentioning
confidence: 99%
“…All included studies were written in English. In addition, two studies were conducted in Iran, 22,26 two in Saudi Arabia, 27,28 two in the U.S., 29,30 two in the Netherlands, 31,32 one in Italy, 33 one in Switzerland, 25 and one in the Gaza Strip. 34 Besides, the location was not specified in one study ( Table 1).…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…Evidence has indicated that operating room personnel were affected by musculoskeletal pain (58-90%) after a year of clinical work. 25 The limited studies performed on operating room personnel around the world have also revealed the high prevalence of these disorders. However, considering the debatable results obtained in this area, no comprehensive research has been conducted on the prevalence of MSDs among operating room personnel.…”
Section: Introductionmentioning
confidence: 99%
“…Uluslararası literatürde ameliyathane hemşirelerinin kas iskelet sistemi sorunlarını belirlemeye yönelik çeşitli çalışmalar (6,7,10,12,15,19,20) yer alırken; Türkiye'de sağlık çalışanları kapsamında hemşirelerin kas iskelet sistemi sorunlarını saptamaya yönelik sadece birkaç çalışmaya (11,13,21,22) rastlanılmıştır. Bu bağlamda, bu çalışma Türkiye'de ameliyathane hemşirelerinde kas iskelet sistemi ağrılarının görülme sıklığını belirleyen ilk çalışmadır.…”
unclassified